2017
DOI: 10.1111/jan.13395
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized patients’ vs. nurses’ assessments of pain intensity and barriers to pain management

Abstract: Aims: The aim of the study was to identify if nurses and patients equally assessed pain intensity and patient-related barriers to pain management in hospitalized patients.Background: Several studies reported poor to moderate agreement between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…One of the included studies decided to base the pain score on behaviour and expression of patients unable to self‐rate. Pain rating by proxy is difficult . Other possible scorings systems designed for cognitive impaired patients are PAINAD, which address advanced dementia, and Abbey Score which is used especially in movement‐based assessment …”
Section: Discussionmentioning
confidence: 99%
“…One of the included studies decided to base the pain score on behaviour and expression of patients unable to self‐rate. Pain rating by proxy is difficult . Other possible scorings systems designed for cognitive impaired patients are PAINAD, which address advanced dementia, and Abbey Score which is used especially in movement‐based assessment …”
Section: Discussionmentioning
confidence: 99%
“…The results of applying the scale also showed that, of all pain management practices, nurses carry out mostly pharmacological interventions. This finding, which several studies sustain, is mainly because this is an interdisciplinary intervention and that there are difficulties in implementing other pain management measures, such as non--pharmacological interventions and pain assessments (which include initial assessment, planning, education, recording, and reassessment; Becker et al, 2017;Dequeker, Van Lancker, & Van Hecke, 2018;Gan et al, 2018). Pain assessment is recognized in the scientific literature as a challenge, pain education and intervention planning being the most neglected areas in clinical practice (Araujo & Romero, 2015;Medrzycka-Dabrowka, Dąbrowski, Gutysz-Wojnicka, Gawroska-Krzemińska, & Ozga, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The agreement between the actual pain levels was considered to be moderate, suggesting room for improvement of nurses' pain assessment techniques. This study suggests that assessment techniques can be improved, particularly when caring for the elderly and females (Dequeker et al, 2018).…”
Section: Pain Assessmentmentioning
confidence: 93%
“…In a study completed by Dequeker, Van Lancker, and Van Hecke (2018), pain intensity described by patients was compared with the pain assessment completed by nurses. The validated instrument used by patients in this study included the numeric pain scale ranging from zero to ten.…”
Section: Pain Assessmentmentioning
confidence: 99%